The Moderating Effects of Cognitive Complexity and Prior Product Familiarity on the Predictive Ability of Selected Multi-Attribute Choice Models for Three Consumer Products - TAN, Chin Tiong (Institutional Knowledge at Singapore Management University, 1981)
Respondents were classified according to their levels of cognitive complexity and product familiarity with three consumer products: automobiles, apartments, and toilet soaps. Using repeated measures and the reperatory grid technique with ten brands and ten dimensions for each product class, five multi-attribute models are tested for predictive accuracy of rank order brand preferences. Three sets of 2×2×5 ANOVA studies showed significant systematic relationships between type of model and level of cognitive complexity and significant differences attributed to models across all products and to cognitive complexity for two of the three products. [ABSTRACT FROM AUTHOR]